Knowledge management systems success model for higher education institutions: a partial least square approach - Ali, Nor’ashikin; Che Cob, Zaihisma; Sulaiman, Hidayah (2016)
The implementation of Knowledge Management (KM) in various organizations including higher education institutions (HEIs) have provided significant benefits in making the best use of knowledge in meeting organizational strategic objectives.This study reports the findings of the factors that influence the success of knowledge management systems (KMS) in higher education institutions (HEIs).The KMS success model for HEIs was proposed and tested to 204 academicians in Malaysian public universities using partial least square approach. Out of seventeen hypotheses, fifteen hypotheses were supported. It was found that perceptions of usefulness of KMS and satisfaction levels of academicians play important roles in determining KMS success in higher education.These perceptions require the support of organizational factors such as leadership, incentive, culture of sharing, subjective norm, and training.The KMS success model developed in this study can help stakeholders in implementing successful KMS in higher education.